2013
DOI: 10.1039/c2ra21906a
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of solid trivalent metal dodecyl sulfates: from aqueous solution to lamellar superstructures

Abstract: Metal dodecyl sulfates of trivalent aluminium, chromium, lanthanum and gadolinium were prepared by addition of the corresponding salts to aqueous solutions of sodium dodecyl sulfate at the natural pH (ca. 6). Using X-ray diffraction, FT-IR and NMR spectroscopy, DSC, thermogravimetry and polarizing light thermomicroscopy it is shown that metal dodecyl sulfates are formed with lamellar structures. These have different degrees of hydration, which depend upon the metal ion. In some cases there is evidence for coex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 86 publications
1
7
1
Order By: Relevance
“…This is also suggested by the computation of the binding ratio ([SDS]/[TMePyPI 4 ]) equal to 3.1. This value although slightly lower than that expected for full charge neutralization may suggest that the structure of the aggregate also takes into consideration the hydrophobic chain of the surfactant, as suggested by previous studies on similar systems [30]. However, at binding ratios higher than the stoichiometric ones, the DS − -TMePyP +4 aggregates re-dissolve and the electrical conductivity of mix solution is somewhat similar to that observed for SDS in aqueous solution.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…This is also suggested by the computation of the binding ratio ([SDS]/[TMePyPI 4 ]) equal to 3.1. This value although slightly lower than that expected for full charge neutralization may suggest that the structure of the aggregate also takes into consideration the hydrophobic chain of the surfactant, as suggested by previous studies on similar systems [30]. However, at binding ratios higher than the stoichiometric ones, the DS − -TMePyP +4 aggregates re-dissolve and the electrical conductivity of mix solution is somewhat similar to that observed for SDS in aqueous solution.…”
Section: Resultssupporting
confidence: 73%
“…Besides, β values do not change with temperature. From a nominal analysis of the β values, we can conclude that the experimental β values are lower than the expected value for charge neutralization; this discrepancy may indicate that the aggregate structure is rather complex, which, on the other hand, is justified to avoid the exposition of hydrophobic chains of surfactant to water [30]. This has also been found for interaction between trivalent metal ions and long chain carboxylates [31,32] and alkylsufates [30].…”
Section: Figure 1 In Herementioning
confidence: 78%
“…Recently we have found that the use of ionic surfactants can lead to the formation of organized structures with, for example, trivalent metal ions [22]. Herein we describe the effect of N-alkyltrimethylammonium surfactants, with different alkyl chain lengths (12 and 16 methylene groups), either in unimer or micelle forms, on the equilibrium between the different possible species of meso-substituted porphyrin, in aqueous solution, using spectroscopic techniques.…”
Section: Introductionmentioning
confidence: 98%
“…With SDS, the maximum interaction concentration is not reached at charge neutralization, but at higher r values. This leads to formation of a lamellar solid [65], which redissolves in excess surfactant due to preferential hydrophobic interactions between the alkyl chains of the surfactant, destabilizing the aggregates of dodecylsulfate (DS − )/metal ion. The fact that lead(II)…”
Section: Lead(ii) Interactions With Sdsmentioning
confidence: 99%